Aprendizagem interorganizacional: o caso da rede de cooperativas de catadores de material reciclável - Catabahia - Silva, Gislane Santos (2015)
The business networks have emerged as a new organizational setting in order to increase the competitiveness of companies and as alternative to achieve their goals. Some studies show that cooperation between the companies involved in network, generate benefits through the exchange of information and knowledge. The analysis of learning strategies used by organizations can result in a better way of understanding in which learning takes place the cooperation networks. This study investigates which the conditions for waste pickers cooperatives learn how participants Catabahia network, and identify the main reasons for that cooperatives integrate the network, verify the interorganizational learning strategies adopted by cooperatives, types of knowledge learned and the benefits from the network learning process. The research strategy adopted was the single case study, with data collection in 9 cooperatives, considered as small units of analysis: members of Catabahia Network. To collect data, it was used a semi-structured interview guide, applied with representatives and technicians of cooperatives. In addition to, we used the techniques of documentary analysis and direct observation. From the analysis of the data was verified that cooperatives join the network as a way to formalize and get benefits. As for learning strategies, it was found that cooperatives adopt a collaborative behavior, commitment strategies, collaboration and accommodation. Regarding the types of knowledge, it is observed that cooperatives have a tacit knowledge of previous experience, and get explicit knowledge through training and training received by the technicians. The results indicate that the main benefits generated by learning were: the development of managerial skills and representation, capacity to participate in tenders and projects and identify more clearly the needs of cooperatives.